2010
DOI: 10.1088/0957-4484/21/18/185304
|View full text |Cite
|
Sign up to set email alerts
|

Microdomain orientation dependence on thickness in thin films of cylinder-forming PS-b-PMMA

Abstract: The self-assembly of block-copolymer thin films in periodic nanostructures has received considerable attention during the last decade due to their potential applications in nanofabrication and nanolithography. We followed the morphologies developed in thin films of a cylinder-forming diblock copolymer polystyrene-b-poly(methylmethacrylate) ((PS-b-PMMA), PS 46.1 kg mol( - 1), PMMA 21.0 kg mol( - 1), lattice spacing L(0) = 36 nm), as a function of the film thickness (t), analyzing the effect of thickness commens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 36 publications
4
31
3
Order By: Relevance
“…These BCP films were thermally annealed at 280 °C for 60 min in a nitrogen atmosphere, giving a final thickness of 30 nm that is ideal for the formation of half-cylinder structures [28]. The equilibrium period (L 0 ) and correlation length were determined for each type of sub-layer using fast Fourier transform (FFT) analysis of a low-magnification atomic force microscopy (AFM) image.…”
Section: Resultsmentioning
confidence: 99%
“…These BCP films were thermally annealed at 280 °C for 60 min in a nitrogen atmosphere, giving a final thickness of 30 nm that is ideal for the formation of half-cylinder structures [28]. The equilibrium period (L 0 ) and correlation length were determined for each type of sub-layer using fast Fourier transform (FFT) analysis of a low-magnification atomic force microscopy (AFM) image.…”
Section: Resultsmentioning
confidence: 99%
“…This report also commented on highly ordered pattern formation irrespective of substrate as confi rmed by simulation data. This is an important point as this particular PS-b -P2VP-b -PtBMA tri-BCP avoided complex brush modifi cations unlike those required for di-BCP counterparts, e.g., PS-b -PMMA [ 191 ] or PS-b -PDMS. [ 192 ] A work by Aizawa et al [ 193 ] in 2006 demonstrated the patterning of two metals at substrate surfaces using aqueous metal reduction and a PS-b -P2VP-b -PEO system, however, ordered uniform patterns were not formed.…”
Section: Triblock Copolymers and Inorganic Incorporationmentioning
confidence: 98%
“…The annealing was performed under vacuum (p = 3 9 10 -2 mbar) at 190°C for 2 h to promote self-organization into hexagonal arrangements of PMMA cylinders in a PS matrix with diameter (d) and lattice spacing (L 0 ) ( Fig. 1b) dictated by the molecular weight of the specific macromolecule (Zucchi et al 2010). Exposure under an ultraviolet lamp (5 mW/cm 2 , k = 253.7 nm, 90 min) degraded the PMMA and cross-linked the PS matrix.…”
Section: Polymeric Mask Preparationmentioning
confidence: 99%